Computational design and molecular insights into acetylcholinesterase inhibitors from Aristolochia indica for Alzheimer’s disease therapy - Srinivasarao Mande; Lalitha Repudi; Sanchari Goswami; Nadia Psalms Gangavarapu; Hamid Ghaffoori Hasan; Kumaraswamy Gandla (Discover Chemistry)
Abstract Alzheimer’s disease (AD) remains a major neurodegenerative disorder with limited effective treatments, necessitating the search for novel acetylcholinesterase (AChE) inhibitors to mitigate cognitive decline. While synthetic inhibitors pose concerns regarding toxicity and bioavailability, natural compounds from Aristolochia indica present a promising yet underexplored alternative. This study employed molecular docking, molecular dynamics (MD) simulations, and in silico drug-likeness and ADME profiling to evaluate fourteen bioactive compounds against human AChE (hAChE, PDB: 6O4W) and Torpedo californica AChE (TcAChE, PDB: 1EVE). Docking analysis revealed binding affinities ranging from − 8.2 to − 11.2 kcal/mol (hAChE) and − 8.1 to − 11.2 kcal/mol (TcAChE), with Cepharadione A (NP1) exhibiting the highest affinity (− 11.2 kcal/mol) via multiple stabilizing interactions within the active site. MD simulations confirmed the structural stability of NP1, NP2 (Savinin), and NP3 (Aristolactam II) complexes, with RMSD < 2.0 Å over 100 ns. Drug-likeness and ADME evaluations indicated favorable pharmacokinetic properties, including optimal lipophilicity (LogP 1.84–5.0), high gastrointestinal absorption, and blood–brain barrier permeability. Most compounds demonstrated minimal P-glycoprotein efflux and selective metabolism via cytochrome P450 enzymes, supporting their CNS drug potential. Quantum chemical calculations further corroborated electronic stability and reactivity. These findings highlight A. indica-derived compounds as promising AChE inhibitors, addressing the need for safer and more effective natural alternatives for AD therapeutics and warranting further experimental validation. Graphical Abstract